(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
This research seeks to identify the specificity of the geographical space among the Muqata’at poets in the Umayyad era. The relationship of these poets with the geographical space was different from the usual and familiar ones that are commonly found in poetry in general, due to the specificity of the lives of the Muqata’at poets in general, who lived a life of endorsement and rebellion, and they suffered the consequences of fleeing from authority and separation from society, so the geographical space represented a haven in which they discharged their energies and broadcast their feelings and sensations in it. This signalled the establishment of new relationships with the elements of nature in its various manifestations, especially the geographical space; a relationship that foreshadows the extent of the alienation that these poets suffered in their native society, so that the geographical space becomes a substitute for society, and opens up to the elements of familiarity, warmth and security that they were deprived of in their social environment.